The Influence Of Service Quality And Location On Purchasing Decisions In Coffee Shop Ngupi Dija - Afrillia Siska Sari; Defrizal Defrizal (Cita konsultindo, 2025)
This research purpose to analyse the influence at service quality and location at purchasing decisions in the Ngupi Dija Coffee Shop. Service quality and location are important factors in attracting consumer interest and increasing customer loyalty. This study utilize a quantitative oncoming with a survey method from distributing questionnaires for a number of respondents who have made purchases at the Ngupi Dija Coffee Shop. Data analysis was carried out using multiple linear regression to determine the influence at any variable. The research outcome indicate lest service quality have a positive and significant influence at purchasing decisions, where good service is able to encourage consumers to make repeat purchases. Location has also been sure for has a positive and significant influence at purchasing decisions, with strategic, convenient and easily accessible locations being the main factors in attracting customers. Simultaneously, service quality and location have a significant influence on purchasing decisions. In conclusion, improving service quality and choosing a strategic location can be an effective strategy to improve consumer purchasing decisions. This study also provides recommendations for Ngupi Dija Coffee Shop managers to continue to improve service quality, provide training for employees, and ensure that location facilities meet customer need